Multimorbidity and care dependence in older adults: a longitudinal analysis of findings from the 10/66 study - Jianan Bao; Kia-Chong Chua; Matthew Prina; Martin Prince (BMC, 2019)
Abstract Background In an ageing world facing an epidemic of chronic diseases, there is great interest in the burden of multimorbidity on individuals and caregivers, yet no studies have examined the longitudinal association between multimorbidity and care dependence in low and middle income countries. Mental and cognitive disorders are associated with dependence but little is known about their role in the pathway to dependence in the context of multimorbidity. This study aims to determine (1) the association of multimorbidity with the onset of care dependence in older adults, accounting for mortality and controlling for sociodemographic factors, and (2) the independent effects of physical multimorbidity, mental and cognitive disorders. Methods A population-based cohort study of people aged 65 years and older in six countries in Latin America, and China. Data on chronic conditions and sociodemographic factors were collected at baseline. Multimorbidity was ascertained as a count of up to 15 mental, cognitive and physical health conditions. Dependence was ascertained through informant interviews at baseline and follow-up. We used competing risk regression to assess the association between multimorbidity and the onset of care dependence, acknowledging the possibility of dependence-free death. We also assessed the independent effects of physical multimorbidity and depression, anxiety and dementia individually. Results 12,965 participants, with no needs for care at baseline, were followed up for a median of 3.0-4.9 years. Each unit increase in multimorbidity count increased the cumulative risk of dependence by 20% in the fully adjusted model. Age was the only variable to confound this relationship. Physical multimorbidity was associated with only a modest increased risk of care dependence. Dementia, depression and anxiety were independently associated with incident care dependence at every level of physical multimorbidity, and depression and anxiety attenuated the effect of physical multimorbidity. Conclusion Multimorbidity consistently predicts care dependence with little variation between countries. Physical multimorbidity imparts a lower risk than multimorbidity with mental and cognitive disorders included. Mental and cognitive disorders independently increase the risk of care dependence. Comprehensive and holistic assessment of disorders of body, brain and mind can help to identify older people at high risk of care dependence.